Findings of marine reptilesin the Upper Cretaceous of Middle Urals - V. M. Efimov; A. I. Malikov (Известия высших учебных заведений: Геология и разведка)
The first description of the complex of bones from one individual plesiosaur marine reptile from the Upper Cretaceous deposits of the Central Urals is done; the reptiles remains of different species encountered in these sediments so far. The new finding comes from the neighborhood of Kamensk-Uralsky, Sverdlovsk Region. Earlier, these representatives of the Late Mesozoic marine life were not known. The research was conducted by Undory paleontological museum in cooperation with regional specialists of the Middle Urals.